Effect of soil amendments and nano and conventional nitrogen on potato yield and tuber quality - Wissam, H A; Bassam, R S (Plant Science Today, 2026)
Soil amendments improve the chemical and fertility properties of soil, such as soil pH and cation exchange capacity and chelate nutrients, especially nitrogen, thereby preventing their loss through leaching or volatilisation. A field trial was conducted during the spring growing season of 2025 in soil with a silty loam texture to evaluate the effects of soil amendments, namely zeolite, perlite, palm frond residues and palm frond biochar in combination with different levels were symbolised as A1, A2, A3, A4 and A0 respectively, and forms of nitrogen (100 % conventional urea), (50 % conventional urea), (100 % nano nitrogen) and (50 % nano nitrogen) which were symbolised as N1, N2, N3, N4 and N0 respectively. The study aimed to assess several yield and quality parameters of potato using a randomised complete block design (RCBD) with 3 replicates (75 experimental units). Statistical analysis revealed that biochar produced the highest mean values for dry matter percentage, starch percentage in tubers, average weight of marketable tuber and marketable yield, with values of 18.40 %, 12.40 %, 112.98 g tuber-1 and 42.592 mg ha-1 respectively. Palm frond residues resulted in the highest protein percentage (11.43 %). The nitrogen treatment with 100 % nano nitrogen produced the highest average dry matter percentage, starch percentage and protein percentage in tubers, average weight of marketable tuber and marketable yield (19.28 %, 13.18 %, 15.40 %, 119.30 g tuber-1 and 47.777 mg ha-1 respectively). Overall, the results demonstrated the superiority of biochar and nano-nitrogen treatments.